Perancangan Aplikasi Inventarisasi Alat / Barang Di Dinas Komunikasi Dan Informatika Kota Palembang Berbasis Web Dengan Metode Action Research - Ardiansyah Putra (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2022)
Proper management of goods will make it easier for us to manage the assets owned by an organization. By utilizing existing technology, the management of tools/goods will be easier to do and of course will be more professional. Thus, one will be able to avoid waste resulting from the loss of assets owned due to poor management of the equipment/goods. Currently, the Palembang City Communication and Information Office is already using a digital inventory of goods. However, the system is still used by the E-Government Sector and has not been fully implemented in one application by all fields at the Palembang City Communications and Information Office. Thus, this research is expected to produce an application that can be used as a whole by all fields in the Palembang City Communications and Information Office, so that the equipment and goods at the Palembang City Communications and Information Office can be monitored in a more professional and accountable manner